Physicochemical property changes and volatile analysis for torrefaction of oil palm frond - Fakhrur Razil Alawi, Abdul Wahid; Nur Hazirah Huda, Mohd Harun; Siti Raishan, Mohd Rashid; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (The Italian Association of Chemical Engineering - AIDIC, 2017)
Torrefaction is an upgrading technique for biomass properties which involves the heating of biomass to moderate temperatures typically between 200 and 300 °C in an inert condition. Torrefied biomass has darker colour, high energy density, high heating value and exhibits hydrophobic characteristic that makes it easier for grinding. Therefore, the aim of this work is to conduct an experimental work in order to study the torrefaction effects on the physicochemical properties of oil palm frond (OPF) as well as to identify the evolution of volatiles composition during the torrefaction. Torrefaction experiments were performed at four different temperatures (240 – 330 °C) and three different residence times (15, 30 and 60 min). The higher heating value of raw and torrefied biomass were measured to establish a relationship between energy loss and mass loss during torrefaction. Scanning electron microscope (for physical analysis) was used to study the structure of raw and torrefied OPF. Elemental analysis was carried out by using Carbon, Hydrogen. Nitrogen and Sulphur (CHNS) analyser and the proximate analysis were measured based on the method specified by American Society for Testing and Materials (ASTM). Condensable and non-condensable gases were analysed by using high performance liquid chromatography (HPLC) and gas chromatography thermal conductivity detection (GC-TCD) respectively. Higher torrefaction temperature and longer residence time leads to severe decomposition which reduces the mass yield of the torrefied oil palm frond but increases the heating value of torrefied OPF. The carbon content increases with the increasing of temperature and residence time, while hydrogen and oxygen contents are decreases. The values of fixed carbon and ash content increases, while volatile matter value decreases when the oil palm frond is torrefied for a longer time at high temperature. For volatile release, carbon monoxide and carbon dioxide are the major compounds presence in non-condensable gas and traces of methane was only identified when OPF was torrefied at 300 °C and 330 °C. Acetic acid and methanol are the major compounds of condensable gases with the presence of formic acid and lactic acid at 330 °C. It can be concluded that high temperature gives significant effect on the chemical reaction for formation of condensable and non-condensable gases.